“APERTURA-APRETURA-CERRADURA”: CRISIS, SOCIAL PROTESTS AND LIMITED OPENING 1981-1985. - Assis dos Santos, Eric (Revista de Historia Social y de las Mentalidades, 2015)
This article aims to analyze the process of liberalization limited Pinochet and the Chilean Armed Forces in 1981-1985. Through reports, speeches, press and official documents, we targeted identifying actors and circumstances that created the first good chance of overthrowing the Chilean dictatorship. To this end, we try to analyze the process of democratic transition from a perspective that combines social demands of the 1983-1984 protests and internal debates of the Pinochet government.